Regional citrate anticoagulation in CVVH: A new protocol combining citrate solution with a phosphate‐containing replacement fluid. Issue 2 (7th August 2012) - Morabito, Santo; Pistolesi, Valentina; Tritapepe, Luigi; Zeppilli, Laura; Polistena, Francesca; Fiaccadori, Enrico; Pierucci, Alessandro
Abstract Regional citrate anticoagulation (RCA) is a valid anticoagulation method in continuous renal replacement therapies (CRRT) and different combination of citrate and CRRT solutions can affect acid‐base balance. Regardless of the anticoagulation protocol, hypophosphatemia occurs frequently in CRRT. In this case report, we evaluated safety and effects on acid‐base balance of a new RCA‐ continuous veno‐venous hemofiltration (CVVH) protocol using an 18 mmol/L citrate solution combined with a phosphate‐containing replacement fluid. In our center, RCA‐CVVH is routinely performed with a 12 mmol/L citrate solution and a postdilution replacement fluid with bicarbonate (protocol A). In case of persistent acidosis, not related to citrate accumulation, bicarbonate infusion is scheduled. In order to optimize buffers balance, a new protocol has been designed using recently introduced solutions: 18 mmol/L citrate solution, phosphate‐containing postdilution replacement fluid with bicarbonate (protocol B). In a cardiac surgery patient with acute kidney injury, acid‐base status and electrolytes have been evaluated comparing protocol A (five circuits, 301 hours) vs. protocol B (two circuits, 97 hours): pH 7.39 ± 0.03 vs. 7.44 ± 0.03 (P < 0.0001), bicarbonate 22.3 ± 1.8 vs. 22.6 ± 1.4 mmol/L (NS), Base excess −2.8 ± 2.1 vs. −1.6 ± 1.2 (P = 0.007), phosphate 0.85 ± 0.2 vs. 1.3 ± 0.5 mmol/L (P = 0.027). Protocol A required bicarbonate and sodium phosphate infusion (8.9 ± 2.8 mmol/h and 5 g/day, respectively) while protocol B allowed to stop both supplementations. In comparison to protocol A, protocol B allowed to adequately control acid‐base status without additional bicarbonate infusion and in absence of alkalosis, despite the use of a standard bicarbonate concentration replacement solution. Furthermore, the combination of a phosphate‐containing replacement fluid appeared effective to prevent hypophosphatemia.